A Contribution to the Analysis of Determining the Post-collision Vehicle Speed - Bukljaš, Zdravko; Radoš, Jerko; Zovak, Goran (Promet - Traffic&Transportation, 2012)
About 50% of the analyses of actual road traffic accidentsare the analyses of various collision conditions of vehicles, i.e.various collisions of two vehicles or crashes of vehicles intovarious types of solid barriers. Such analyses, however, requirethat the values of vehicle post-collision movement parametersof its kinematics are determined with as much accuracy as possible.Since methods commonly LLSed in the present forensic expertisedo not provide satisfactory results by not taking into accountall the elements of the vehicle movement, this paper presentsanalytic considerations of the issue, thus determining relativelysimple and for the practice acceptable analytical expressionswhich can be LLSed to detennine the vehicle movement parametersimmediately following collision.